2008
DOI: 10.1016/j.gloenvcha.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The drivers of Chinese CO2 emissions from 1980 to 2030

Abstract: China's energy consumption doubled within the first 25 years of economic reforms initiated at the end of the 1970s, and doubled again in the past 5 years. It has resulted of a threefold CO 2 emissions increase since early of 1980s. China's heavy reliance on coal will make it the largest emitter of CO 2 in the world. By combining structural decomposition and input-output analysis we seek to assess the driving forces of China's CO 2 emissions from 1980 to 2030. In our reference scenario, production-related CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
225
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(258 citation statements)
references
References 29 publications
4
225
0
1
Order By: Relevance
“…For example, the rise in CO 2 emissions that would result if China's household consumption patterns converge with current US levels could not be offset by efficiency gains alone 4 . Promoting low-carbon lifestyles is mentioned in the plan only in passing and without concrete measures or targets for how they might be achieved.…”
Section: Government Goalsmentioning
confidence: 99%
“…For example, the rise in CO 2 emissions that would result if China's household consumption patterns converge with current US levels could not be offset by efficiency gains alone 4 . Promoting low-carbon lifestyles is mentioned in the plan only in passing and without concrete measures or targets for how they might be achieved.…”
Section: Government Goalsmentioning
confidence: 99%
“…It is common to deal with this issue using the average of all n! possible equivalent exact decomposition forms to achieve the final ideal decomposition [14,15,20,49,50]. Subsequently, changes of carbon dioxide emissions induced by each category of final demands consumption have been widely performed [14,21,51,52].…”
Section: Structural Decomposition Analysis (Sda)mentioning
confidence: 99%
“…Zhu et al adopted IO-SDA method to investigate the indirect carbon emissions from residential consumption in China from 1992 to 2005 [18], results show that the rising residential consumption level accelerated the growth of residential indirect carbon emissions. By combining structural decomposition and input-output analysis framework, Guan et al found that efficiency gains in production sectors could not cope with the increasing emissions in China from 2002 to 2005 [19]; they then forecasted that household consumption, capital investment and exports growth would largely increase the carbon emissions up to 2030, while efficiency gains would partially offset the projected increases [20]. Minx et al used structural decomposition analysis to update Peters' previous analysis of China's carbon emissions and found that efficiency improvements have largely offset additional CO2 emissions from increased final consumption with special focus on the period 2002 to 2007 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Based on current knowledge of emission status, understanding the driving forces behind the increase in CO2 emissions in cities is the foundation for the presentation of a comprehensive analysis on future emissions, and it is essential to the formulation of policies for the mitigation of the effects of climate change and fulfilment of applicable targets. The relative contributions of socioeconomic factors such as population, economic growth, energy structure, and energy intensity to the change in CO2 emissions in China have been analyzed [7][8][9][10][11][12]. The objectives of this study are to quantify and examine the driving forces behind CO2 emissions in Tianjin by applying the extended Logarithmic Mean Divisia Index (LMDI) decomposition model and, based on this, to make policy recommendations to help achieve the stated emission reduction targets.…”
Section: Introductionmentioning
confidence: 99%